Implementación de una solución para el manejo de ciclo de vida de aplicaciones (alm), utilizando metodología scrum y tfs como core central de la solución, para la optimización del proceso de desarrollo de software, en la empresa Grupo Babel del Ecuador en la ciudad de Latacunga en el periodo agosto – diciembre 2015 - Merlo Vega, Santiago (2016)
The present research has as main objective, to implement a management solution of Lifecycle of Application (ALM), in the Grupo Babel Ecuador company, using Microsoft specifically Team Foundation Server as a central core of this solution, tools and scrum as a methodology, which allows us to provide a solution that facilitates the development process in the company, optimizing time, quality, and greater traceability at every stage of the development process. Applicants, used for the theoretical foundation, literature, virtual research and field research to obtain the data for later analysis technique is applied to the instrument the survey questionnaire. Following data collection, through the survey apply by the employees of the Grupo Babel Ecuador company the analysis and interpretation of the results is carried out, which makes evident, that there is not a tool for Lifecycle of Application….